Ammonium‐Iron(III) metallacryptate inclusion complexes based on Aroylbis(N, N‐diethylthioureas): Synthesis and structure. Issue 5 (7th August 2022) - Huy, Nguyen Hung; Abram, Ulrich; Thang, Pham Chien
Abstract: One‐pot reactions of pyridine‐ or catechol‐scaffolding aroylbis( N, N ‐diethylthioureas), H2 L 1 or H2 L 2, with methanolic solutions of FeCl3 and NH4 Cl bring about novel cationic ammonium‐inclusion complexes NH4 ⊂ [Fe2 (L)3 ] + (L = L 1 or L 2 ), which could be separated as PF6 – salts. The inclusion compounds have been characterized by elemental analyses and spectroscopic methods such as HRMS, IR and SCXRD. Ammonium ions are captured in the intramolecular voids of 2‐metallacryptands [Fe2 (L)3 ] (L = L 1 or L 2 ) resulting from the octahedral coordination of Fe 3+ ions with aroylthiourea moieties of the ligands. Hydrogen bonds are established between the NH4 + ions and the donor atoms of the cages. Abstract :